GUT DYSBIOSIS AND GENERALIZED ANXIETY DISORDER: A SYSTEMATIC REVIEW - Senft, Charline Aline; Gonçalves, Jamili; Werner, Marina (Seven Editora, 2024)
Generalized Anxiety Disorder (GAD) is manifested by symptoms such as tension, fatigue, and negative thoughts, and can be influenced by diet. Diets high in fat and low in vitamins B2, B6 and B9 can alter the gut microbiota, causing dysbiosis, which affects the gut-brain axis, a communication pathway between gut and brain. This dysbiosis increases intestinal permeability and inflammation, impacting mood and anxiety. Therefore, the objective of this study was to search the most recent literature for studies that correlate the gut microbiota with mental health. This is a descriptive and exploratory study, carried out through a systematic review with articles published between 2014 and 2024, found in databases such as PubMed, BVS, and Google Scholar. The research used the PICO strategy, using descriptors such as "Gut microbiota", "Dysbiosis" and "Anxiety", combined by Boolean operators. The studies highlight the complex relationship between gut microbiota and mental health, showing that probiotics can reduce symptoms of anxiety and depression, although the results are more consistent for anxiety. Probiotics modulate inflammation and regulate serotonin, which is essential for emotional well-being. Dysbiosis, associated with poor diet or stress, reduces serotonin and increases inflammatory cytokines, aggravating mental symptoms. The connection between microbiota, the immune system, and mental health offers new therapeutic approaches, but more research is needed to advance this field. DOI:https://doi.org/10.56238/sevened2024.037-038